On reading books to children : parents and teachers - Van Kleeck, Anne.; Stahl, Steven A.; Bauer, Eurydice B. (Eurydice Bouchereau) (Mahwah, N.J. : L. Erlbaum Associates, 2003)
Publisher's description: On Reading Books to Children: Parents and Teachers brings together in one volume current research on adult book reading to children. The authors, drawn from around the world, are key researchers and eminent scholars from the fields of reading and literacy, child language, speech pathology, and psychology, representing multiple perspectives within these disciplines. Chapters on the effects and limitations of book sharing are integrated with chapters discussing promising programs on storybook research. The reality of reading to children is more complex than it appears on the surface. The authors discuss some effects of and suggestions for reading to children that have emerged from the research. The ideas set forth in this volume will stimulate new lines of research on the effects of storybook reading, as well as refinements of current methods, yielding findings that enrich our understanding of this important arena of literacy development.
Social-emotional requisites for learning to read / Adriana G. Bus -- Learning words from books / Jeanne De Temple, Catherine E. Snow -- Diversity in adults' styles of reading books to children / Elaine Reese, Adell Cox, Diana Harte, Helena McAnally -- Book sharing with preschoolers with language delays / Anne van Kleeck, Judith Vander Woude -- A framework for examining book reading in early childhood classrooms / David K. Dickinson, Allyssa McCabe, Louisa Anastasopoulos -- Reading aloud to young children as a classroom instructional activity : insights from research and practice / William H. Teale -- The nature of storybook reading in the elementary school : current practices / Lesley Mandel Morrow, Rebecca Brittain -- Taking advantage of read-alouds to help children make sense of decontextualized language / Margaret G. McKeown, Isabel L. Beck -- Dialogic reading : a shared picture book reading intervention for preschoolers / Andrea A. Zevenbergen, Grover J. Whitehurst -- Storybook reading in a multicultural society : critical perspectives / Jim Anderson, Ann Anderson, Jacqueline Lynch, Jon Shapiro -- Reading, homes, and families : from postmodern to modern? / Victoria Carrington, Allan Luke -- Storybook reading and young bilingual children : a review of the literature / Rosalinda B. Barrera, Eurydice Bouchereau Bauer -- Research on book sharing : another critical look / Anne van Kleeck -- Joint reading as a context : explicating the ways context is created by participants / A.D. Pellegrini, Lee Galda -- Parent-child storybook reading as a complex adaptive system : or "an igloo is a house for bears" / David B. Yaden, Jr. -- What do we expect storybook reading to do? : how storybook reading impacts word recognition / Steven A. Stahl.
Includes bibliographical references and indexes.
Keywords: Oral reading; Storytelling; Children -- Books and reading